S-Bend Silicon-On-Insulator (SOI) Large Cross-Section Rib Waveguide for Directional Coupler - Nurdiani Zamhari; Abang Annuar Ehsan; Mohd Syuhaimi Abdul Rahman (Institute of Advanced Engineering and Science, 2017)
S-bend contributes the high losses in the silicon-on-insulator (SOI) large cross-section rib waveguide (LCRW). The objective of this work is to investigate S-bend SOI LCRW with two different single-mode dimensions named symmetrical and asymmetrical. The S-bend SOI LCRW has been simulating using beam propagation method in OptiBPM software. The asymmetrical waveguide with two different dimension arc given the best performance if compared to others dimension with 3 µm of waveguide spacing. It achieved 92.24% and 91.10% of normalized output power (NOP) for 1550 nm and 1480 nm wavelength respectively. Moreover, the minimum of S-bend spacing between the two cores is 0.9 µm for both 1550 nm and 1480 nm. Therefore, asymmetrical waveguide with two different dimension arc and 0.9 µm of S-bend spacing are chosen. This analysis is important to determine the right parameter in order to design the SOI passive devices. However, future work should be done to see the performance by designing the coupler and implement in the real system.